Securitization and the fixed-rate mortgage - Andreas Fuster; James Vickery (Federal Reserve Bank of New York, 2013)
Fixed-rate mortgages (FRMs) dominate the U.S. mortgage market, with important consequences for household risk management, monetary policy, and systemic risk. In this paper, we show that securitization is a key driver of FRM supply. Our analysis compares the agency and nonagency mortgage-backed-securities (MBS) markets, exploiting the freeze in nonagency MBS liquidity in the third quarter of 2007. Using exogenous variation in access to the agency MBS market, we find that when both market segments are liquid they perform similarly in terms of supporting FRM supply. However, after the nonagency market freezes, the share of FRMs is sharply higher among mortgages eligible to be securitized through the still-liquid agency MBS market. Our interpretation is that securitization is particularly important for FRMs because of the prepayment and interest rate risk embedded in these loans. We highlight policy implications for ongoing reform of the U.S. mortgage finance system.
Keywords: E44; G18; G21; 330; mortgage finance; securitization; regression discontinuity design; difference-in-differences